Managing brain-hype: understanding and discriminating overemphasized brain-based allegations - Vassallo, Marta; Picozzi, Mario (Medicina Historica, 2023)
Research about our brain’s function is today essential for the assessment of the human species and for our self-comprehension. However, since the neuroscientific turn took place in several areas of research such as psychology, philosophy, and AI, the consequential interdisciplinarity this event created gave birth to an important phenomenon that is still in place today: neuro-hype or brain-hype. As a matter of fact, we are increasingly overstimulated by brain-based observations, research, and alleged discoveries. But, how much of this hype around our brains is justified? This is an essential question if we aim to assess and understand neuroscientific research today. Therefore, in this work, we analyze this phenomenon and its outcomes by investigating different topics ranging from newspaper titles to the relationship between brains and research. In addition to that, we discuss several theories such as neuroessentialism that have made an attempt to explain and understand this phenomenon, which has important ethical implications concerning both scientists and society in its entirety.